Noroviruses associated with acute gastroenteritis in a children's day care facility in Rio de Janeiro, Brazil - Gallimore, C. I. (2004)
Enteric Virus Unit, Enteric, Respiratory and Neurological Virus Laboratory. Specialist and Reference Microbiology Division. Health Protection Agency. Colindale, London, UK.